34.7k views
0 votes
Identify the factoring pattern: y 2 −16=(y+4)(y−4) y2-16=(y+4)(y-4)

Difference of Squares
Perfect Square Trinomial
Difference of Cubes
Sum of Cubes

2 Answers

1 vote

I think it is the sum of cubes because if you add them, they become cubes.

User Liloka
by
6.3k points
5 votes

This is a difference of squares. Every time you have the difference between two squares, you can factor it as the product between the sum and the difference of the roots:


a^2-b^2 = (a+b)(a-b)

In your case, the squares are


y^2 \to \text{the square of } y


16 \to \text{the square of } 4

So, the difference between the squares,
y^2-16 can be written as the multiplication between the sum and difference of the roots:


y^2-16=(y+4)(y-4)

User T Burgis
by
6.3k points